Pegasus: Load-Aware Selective Replication with an In-Network Coherence Directory - Li, Jialin; Nelson, Jacob; Jin, Xin; Ports, Dan R. K. (University of Washington, 2018)
High performance distributed storage systems face the challenge of load imbalance caused by skewed and dynamic workloads. This paper introduces Pegasus, a new storage architecture that leverages new-generation programmable switch ASICs to balance load across storage servers. Pegasus uses selective replication of the most popular objects in the data store to distribute load. Using a novel in-network coherence directory, the Pegasus switch tracks and manages the location of replicated objects. This allows it to achive load-aware forwarding and dynamic rebalancing for replicated keys, while still guaranteeing data coherence. The Pegasus design is practical to implement as it stores only forwarding metadata in the switch data plane. The resulting system improves the 99% tail latency of a distributed in-memory key-value store by more than 95%, and yields up to a 9x throughput improvement under a latency SLO – results which hold across a large set of workloads with varying degrees of skewness, read/write ratio, and dynamism.